Does cystatin C have an immunomodulatory role in Hashimoto’s thyroiditis? - Söbü, Elif; Yildiz, Zeynep (Journal of Pediatric Endocrinology & Metabolism, 2023)
Studies which report cystatin C's (Cys-C) role in immunological disorders are increasing. However, data in the pediatric age group is limited. In this study, we aimed to evaluate the association between serum Cys-C levels and thyroid autoantibodies in children and adolescents diagnosed with euthyroid Hashimoto's thyroiditis. The patient group was included 50 participants aged between 3 and 18 years, and the control group included 50 healthy children matched for age, gender, and body mass index. Patients with hypothyroidism or taking any medication were not included in the study. Fasting glucose, liver enzymes, urea, creatinine, lipid profile, Cys-C, free thyroxine (fT4), free triiodothyronine (fT3), thyroid-stimulating hormone (TSH), thyroid peroxidase antibody (TPOAb), and thyroglobulin antibodies (TGAb) levels were recorded in all subjects. The mean age of control group was 13.5 ± 2.5 years, and the mean age of Hashimoto thyroiditis (HT) group was 14.2 ± 2.7 years, no statistically significant differences existed (p=0.205). Cys-C values were significantly higher in the HT group than in the control group (p=0.041). When all cases were evaluated, Cys-C levels were statistically positively correlated with fT3, TPOAb, and TGAb values (p<0.001, p=0.029, p=0.013 respectively). Based on the results of our study, Cys-C levels in children and adolescents with euthyroid Hashimoto thyroiditis were statistically higher than their healthy peers. In conclusion, it can be said that Cys-C may be a factor in the etiopathogenesis of autoimmune thyroiditis, and even small changes in TSH values affect Cys-C levels.